Fate of polychlorinated biphenyls in a contaminated lake ecosystem: Combining equilibrium passive sampling of sediment and water with total concentration measurements of biota. (6th October 2015) - Mäenpää, Kimmo; Leppänen, Matti T.; Figueiredo, Kaisa; Mayer, Philipp; Gilbert, Dorothea; Jahnke, Annika; Gil‐Allué, Carmen; Akkanen, Jarkko; Nybom, Inna; Herve, Sirpa
Abstract Equilibrium sampling devices can be applied to study and monitor the exposure and fate of hydrophobic organic chemicals on a thermodynamic basis. They can be used to determine freely dissolved concentrations and chemical activity ratios and to predict equilibrium partitioning concentrations of hydrophobic organic chemicals in biota lipids. The authors' aim was to assess the equilibrium status of polychlorinated biphenyls (PCBs) in a contaminated lake ecosystem and along its discharge course using equilibrium sampling devices for measurements in sediment and water and by also analyzing biota. The authors used equilibrium sampling devices (silicone rubber and polyethylene [PE]) to determine freely dissolved concentrations and chemical activities of PCBs in the water column and sediment porewater and calculated for both phases the corresponding equilibrium concentrations and chemical activities in model lipids. Overall, the studied ecosystem appeared to be in disequilibrium for the studied phases: sediment, water, and biota. Chemical activities of PCBs were higher in sediment than in water, which implies that the sediment functioned as a partitioning source of PCBs and that net diffusion occurred from the sediment to the water column. Measured lipid‐normalized PCB concentrations in biota were generally below equilibrium lipid concentrations relative to the sediment (CLip⇌Sed) or water (CLip⇌W), indicating that PCB levels in the organisms were below the maximum partitioning levels. The present study shows the application versatility of equilibrium sampling devices in the field and facilitates a thermodynamic understanding of exposure and fate of PCBs in a contaminated lake and its discharge course. Environ Toxicol Chem 2015;34:2463–2474. © 2015 SETAC